The Urgency of WhatsApp in Online Learning: Elaboration and Perception of Islamic Religious Education Teachers in Indonesia - Raharjo, Raharjo; Nasikhin, Nasikhin; Supriyono, Widodo (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to analyze the perceptions of Islamic Religious Education teachers regarding the use of WhatsApp as an online learning platform. Using a mixed parallel convergent research method, this research collects quantitative data through surveys, while qualitative data is obtained through in-depth interviews, observation, and documentation studies. This study shows that students in teacher certification programs in Indonesia are heavy users of WhatsApp, as evidenced by 97% of quantitative research respondents spending more than 4 hours per day for academic purposes. With an average standard deviation value of 0.816, this study confirms that students' perceptions of WhatsApp positively impact academic achievement. This is reasonable because they see WhatsApp as having flexibility not limited by place and time; features that are easy to use, integrated with lecture support software; and a fairly strong data security system. In implementing the certification program, WhatsApp's advantages are used to support the success of online classes, such as group discussions, sharing educational knowledge, sharing references, and finding academic agendas. This study also shows that WhatsApp can encourage of Islamic Religious Education teachers to have collaborative skills in teams. However, WhatsApp is still not maximized due to the absence of features for conducting evaluations, a poor learning management system, and the internet in Indonesia, which is not evenly distributed. These findings can be used as a basis for the government to improve the quality of online learning through WhatsApp. Because of its important role in the teacher certification program, we expected that Islamic religious education teachers can use the features in WhatsApp to optimize their use in the academic world